Survival of Patients With Idiopathic Inflammatory Myopathies in Slovenia - Hočevar, Alojzija; Viršček, Andrej; Krošel, Monika; Gradišnik, Suzana; Rotar, Žiga; Tomšič, Matija; Holc, Iztok (Frontiers in Medicine, 2021)
Background: Idiopathic inflammatory myopathies (IIMs) are rare systemic diseases associated with significant morbidity and mortality. The aim of our study was to estimate for the first time the survival of IIM patients in Slovenia. Methods: We included IIM patients diagnosed between January 2005 and December 2020 and followed at two secondary/tertiary rheumatology centers in the country. To study survival/mortality the censor date of April 14 2021 was set. Kaplan–Meier analysis and standardized mortality ratio (SMR) were plotted using data of age and sex matched Slovenian population as a reference. Cox proportional hazards regression analysis was used to study prognostic factors for IIM mortality. Results: During the 16-year observation period, we identified 217 new IIM patients. During follow up 65 (30.0%) patients died. In the first year following IIM diagnosis the SMR was nearly 7-fold higher compared to the matched general population [SMR 6.88 (95%CI 4.41–10.24)] and remained higher also during the following 4 years. However, when excluding IIM patients with cancer, the survival outcome was, except in the first year after IIM diagnosis [SMR 5.55 (95%CI 3.10–9.15)], comparable to matched general population. In addition to cancer [HR 3.71 (95% CI 2.18–6.04)], cardiac involvement [HR 2.18 (95% CI 1.07–4.45)], fever [HR 2.13 (95% CI 1.13–4.03)], and older age [HR 1.07 (95% CI 1.04–1.09)] were extracted as prognostic factors associated with death. Conclusion: The survival of patients with IIM patients was substantially worse compared to matched general population. Cancer was the leading cause of death in our cohort.